Strategic aid allocation in the 21st century: lessons from the 1980?s and 1990 - Verschoor, Arjan (Statistical and Social Inquiry Society of Ireland, 2006)
An evaluation of recipient countries? experience with foreign aid in the 1980s and 90s shows that there is plenty of evidence that policy conditionality has by and large failed, and that there is no evidence that the policy conditions attached to aid have by and large been appropriate. In that light, is the currently advocated move in aid allocation away from policy conditionality and towards selectivity and recipient ownership of its reform programme therefore appropriate? The paper argues that the evidence on aid effectiveness in the 1980s and 90s suggests otherwise.
Symposium on Ireland?s policy to Africa: trade and aid
Read before the Society, 6 April 2006
Keywords: Aid allocation; Strategic aid; 314.15